Optimizing Traditional Shipyard Industry: Enhancing Manufacturing Cycle Efficiency for Enhanced Production Process Performance - Fitriadi, Fitriadi; Ayob, Ahmad Faisal Mohamad (International Journal of Industrial Engineering, Technology & Operations Management, 2023)
The traditional shipbuilding industry is crucial in the global maritime sector, contributing to ship construction, repair, and maintenance. However, it faces challenges in improving production process efficiency. This article explores strategies to optimize the industry's manufacturing cycle. A comprehensive literature review identified key challenges, including production planning errors, coordination issues, material delivery delays, and limited technology integration. These challenges result in higher costs, reduced productivity, and project delays. To address these issues, the article proposes integrating efficient management systems like Lean Manufacturing and Total Quality Management to enhance the production cycle's efficiency. Implementing these systems eliminates non-value-added activities, simplifies processes, and reduces wait times. Additionally, the Manufacturing Cycle Efficiency method is valuable for analyzing production processes, identifying waste, bottlenecks, and interruptions, and optimizing workflows. In conclusion, this article provides insights and strategies to optimize the traditional shipbuilding industry. By integrating efficient management systems, utilizing the MCE method, and embracing sustainability practices, shipyards can enhance production cycle efficiency, increase productivity, and gain a competitive advantage, supporting industry growth and paving the way for a sustainable future.